Implementasi Pendidikan Multikultural di Sekolah Dasar: Studi Kasus di Desa Pancasila Balun Lamongan - Apriliya, Erika Putri; Rosyidi, Zudan (Madrasah Ibtidaiyah Education Journal, 2025)
The purpose of this study is to analyze the implementation of multicultural education at SDN 1 Balun, Balun Village, Lamongan Regency, and to examine the roles of teachers, principals, and the community in fostering the values of diversity and tolerance within the school environment. This study uses a multicultural approach. qualitative with case study method, with data collection techniques through observation, in-depth interviews, and documentation of learning activities and social interactions at school. The results of the study indicate that multicultural education at SDN 1 Balun is implemented contextually through the integration of values such as tolerance, solidarity, and respect for differences in teaching and learning activities, as well as interfaith activities. Teachers act as facilitators of multicultural values, the principal acts as a transformative leader who creates inclusive policies, while community support strengthens the practice of tolerance in schools. Despite obstacles such as differences in parental understanding and limited resources, the implementation of multicultural education at SDN 1 Balun has proven effective in shaping the character of students who are open, respect differences, and strengthen national values ​​in a pluralistic society.